Dioscorea hispida Starch as a Novel Natural Coagulant in Textile Wastewater Treatment - Mohd Suffian Yusoff; Farrandie Juni; Zaber Ahmed; Motasem Azaiza; Hamidi Abdul Aziz (Journal of Engineering and Technological Sciences, 2021)
The process of coagulation-flocculation using Dioscorea hispida starch as a natural coagulant was investigated for the purification of textile effluent from several dyeing and finishing mills. The major parameters tested were COD, turbidity, and color. Prior to conducting the experiments, the general physical characteristics of Dioscorea hispida starch were investigated. The optimal conditions, pH and coagulant dosage were assessed using a jar test. The results demonstrated that the Dioscorea hispida starch yield was 15.38% of Dioscorea hispida dry weight. Pulverizing of Dioscorea hispida mass also resulted in approximately 10-15% of impurities in the final product. The optimal pH of 7 resulted in maximum COD, turbidity and color reductions of 28%, 94% and 64% respectively. The optimum dosage of Dioscorea hispida starch of 2500 mg/L resulted in a maximum reduction of 22%, 93%, 63%, of COD, turbidity, and color, respectively. Overall, this study confirmed that the utilization of Dioscorea hispida starch as a natural coagulant offers a relatively good removal efficiency in textile wastewater treatment.